Evaluación del efecto del uso del kéfir y miel de abeja como suplemento alimenticio en la dieta de pollos de engorde - Paguay Cajas, Diana Mabel (2023)
The objective of this study was to evaluate the effect of kefir and honey as food supplements in the diet of broiler chickens, through productive analysis and immunological parameters. A quantitative descriptive approach was used, using a hypothetical, deductive and experimental methodology. The physical-bromatological composition of honey and kefir was evaluated, and productive variables such as live weight, feed consumption, water consumption, weight gain, feed conversion, morbidity and mortality were measured. In addition, the relationship between these variables and health and immunity was evaluated, evaluating the length of the small intestine, the weight of the viscera such as the bursa of Fabricius, the spleen, the thymus, and determining the serum levels of immunoglobulin A of each group. study. The research was carried out in an experimental shed with 100 birds separated into experimental units of 5 chickens, distributed in 4 groups with 5 repetitions. The treatments implemented included a T0 or control, a T1 with 5% honey, a T2 with 5% kefir and a T3 that combined 5% honey and 5% kefir. The comparative statistical analysis revealed that the live weight of chickens in treatments T1, T2 and T3 was higher than the control group in week 5, with values ranging between 2188g and 2211g. In week 4, feed and water consumption of T1, T2 and T3 resulted in better feed conversion ratios compared to the control group, with values of 1.26, 1.28 and 1.21, respectively. These treatments also showed similar results in terms of weight gain in the same week, which They ranged between 751.4 and 772.8. However, the results regarding the weight and length of the viscera evaluated, as well as mortality and morbidity, were inconsistent.